Recovery of serine protease inhibitor from fish roes by polyethylene glycol precipitation - Hyun Ji Lee; Hyung Jun Kim; Sung Hwan Park; In Seong Yoon; Gyoon-Woo Lee; Yong Jung Kim; Jin-Soo Kim; Min Soo Heu (Fisheries and Aquatic Sciences, 2016)
Abstract The fractionation of serine protease inhibitor (SPI) from fish roe extracts was carried out using polyethylene glycol-4000 (PEG4000) precipitation. The protease inhibitory activity of extracts and PEG fractions from Alaska pollock (AP), bastard halibut (BH), skipjack tuna (ST), and yellowfin tuna (YT) roes were determined against target proteases. All of the roe extracts showed inhibitory activity toward bromelain (BR), chymotrypsin (CH), trypsin (TR), papain-EDTA (PED), and alcalase (AL) as target proteases. PEG fractions, which have positive inhibitory activity and high recovery (%), were the PEG1 fraction (0–5 %, w/v) against cysteine proteases (BR and PA) and the PEG4 fraction (20–40 %, w/v) against serine proteases (CH and TR). The strongest specific inhibitory activity toward CH and TR of PEG4 fractions was AP (9278 and 1170 U/mg) followed by ST (6687 and 2064 U/mg), YT (3951 and 1536 U/mg), and BH (538 and 98 U/mg). The inhibitory activity of serine protease in extracts and PEG fractions from fish roe was stronger than that of cysteine protease toward common casein substrate. Therefore, SPI is mainly distributed in fish roe and PEG fractionation effectively isolated the SPI from fish roes.